Transformation of Human Resources Management to Support Sustainable Bureaucracy Reform in the Makassar Population and Civil Registry Office - Syarifuddin, Syarifuddin (PINISI Discretion Review, 2025)
This study examines how human resource management (HRM) is implemented in the context of ongoing bureaucratic reform at the Population and Civil Registration Office (Discapil) of Makassar City using a qualitative approach and case study method. This study aims to explore in depth the internal dynamics, experiences, and perceptions of stakeholders regarding the challenges and opportunities faced in the implementation of HRM policies. The main focus of this study includes important elements in bureaucratic reform such as the effectiveness of HRM, transparency, efficiency, leadership, and the use of information technology. Data was collected through in-depth interviews with various related parties, including high-ranking officials, department heads, HR staff, lecturers, and educational personnel. Data analysis was conducted using the thematic analysis method, in which data obtained from interviews was organized to identify major themes related to HR management and bureaucratic reform. This process included data coding, grouping themes based on specific patterns, and interpreting the findings. The results of this study reveal several significant issues in human resource management at the Makassar City Discapil, particularly in the context of ongoing bureaucratic reform. Despite efforts to improve the effectiveness and transparency of human resource management, there is dissatisfaction among employees regarding the promotion system, which is considered unclear and lacking in meritocracy. Discapil employees also feel that promotion criteria are not communicated transparently, which fuels distrust in the fairness of the existing promotion system. In addition, access to training and professional development is still limited and uneven, creating gaps in human resource capacity development and affecting employee motivation levels. On the other hand, even though an information technology-based administration system has been implemented, the integration of this technology is still hampered and has not been running optimally. Although the digital-based performance evaluation system has made progress, many employees doubt the objectivity and transparency of employee performance assessments.